genome of Clostridium kluyveri, a strict anaerobe with unique metabolic features - Seedorf, Henning; Fricke, W. Florian; Veith, Birgit; Brüggemann, Holger; Liesegang, Heiko; Strittmatter, Axel; Miethke, Marcus; Buckel, Wolfgang; Hinderberger, Julia; Li, Fuli; Hagemeier, Christoph; Thauer, Rudolf K; et al. (Proceedings of the National Academy of Sciences - PNAS, 2008)
Clostridium kluyveri is unique among the clostridia; it grows anaerobically on ethanol and acetate as sole energy sources. Fermentation products are butyrate, caproate, and H₂. We report here the genome sequence of C. kluyveri, which revealed new insights into the metabolic capabilities of this well studied organism. A membrane-bound energy-converting NADH:ferredoxin oxidoreductase (RnfCDGEAB) and a cytoplasmic butyryl-CoA dehydrogenase complex (Bcd/EtfAB) coupling the reduction of crotonyl-CoA to butyryl-CoA with the reduction of ferredoxin represent a new energy-conserving module in anaerobes. The genes for NAD-dependent ethanol dehydrogenase and NAD(P)-dependent acetaldehyde dehydrogenase are located next to genes for microcompartment proteins, suggesting that the two enzymes, which are isolated together in a macromolecular complex, form a carboxysome-like structure. Unique for a strict anaerobe, C. kluyveri harbors three sets of genes predicted to encode for polyketide/nonribosomal peptide synthetase hybrides and one set for a nonribosomal peptide synthetase. The latter is predicted to catalyze the synthesis of a new siderophore, which is formed under iron-deficient growth conditions.